Unusual Tumors Causing Extrahepatic Portal Venous Obstruction. Issue 3 (1996) - Sharma, B. C.; Saraswat, V. A.; Dhiman, R. K.; Ghoshal, U. C.; Puri, A. S.; Sikora, S. S.
Abstract : Extrahepatic portal vein obstruction has been reported to be associated with tumors of liver, bile ducts and pancreas. We report two cases, one with gastric leiomyosarcoma and another with Non Hodgkin's lymphoma, complicated by portal vein block and presenting with gastric variceal bleeding. Portal vein block in both cases was due to direct vascular infiltration. Development of portal hypertension posed difficulties in management.